Multifunctional nanocatalysts for tandem reactions: a leap toward sustainability - Jagadeesan, Dinesh (Applied Catalysis A-General, 2016)
Design of new multifunctional nanocatalysts is a hot area of research that aims to introduce multiple types of active sites on a single nanocatalyst. Multifunctional nanocatalysts are useful to carry out a multi-step reaction requiring same or different active sites in a single pot. Such catalysts must possess the active sites at spatially distinct locations to avoid neutralization but yet remain active independently or through cooperative actions. The necessity of nanostructuring the active sites have emerged as the key point in a successful design of the catalysts. The review covers the progress in this area of research done in the last five years. It includes the classification of catalysts based on active sites and structure of active sites at the nanoscale. The review covers exhaustively with 250+ references and ample examples to present the concept succinctly. The review covers the evolution of multifunctional catalysts from the perspective of materials chemistry. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heterogeneous catalysts; Multifunctional nanocatalysts; Nanostructured materials; Tandem reactions

Morphology-dependent catalysis by Co3O4 nanostructures in atmospheric pressure carbon dioxide hydrogenation - Gupta, Sharad; Jain, Preeti; Jagadeesan, Dinesh; Vinod, C. P. (Journal of Physical Chemistry C, 2023)
In this work, three Co3O4 nanostructureswith different morphologies (cubes, rods, and sheets) were synthesizedusing a hydrothermal method and tested for the CO2 hydrogenationreaction. The physicochemical properties of the structured Co3O4 were well characterized by X-ray diffraction(XRD), Raman spectroscopy, field-emission scanning electron microscopy(FESEM), transmission electron microscopy (TEM), high-resolution transmissionelectron microscopy (HRTEM), hydrogen temperature-programmed reduction(H-2-TPR), and X-ray photoelectron spectroscopy (XPS) techniques.Based on the characterization, cube, rod, and sheet Co3O4 nanostructures were found to expose the (100), (110),and (112) planes, respectively. The effect of cobalt oxide morphologieswith different exposed surfaces on the activity and selectivity towardCO(2) hydrogenation reaction in a plug-flow reactor operatedbetween 200 and 400 & DEG;C under atmospheric pressure conditionswas explored. The results establish a correlation of the catalyticactivity with morphological structures in the order rods > sheets> cubes. H-2-TPR and XPS studies demonstrated that thehighreducibility of Co3O4 rod makes it an excellentcatalyst for CO2 hydrogenation.